Factors Influencing Youth Participation in Decision Making in Malaysia - Arshad, Rozita; Yeon, Asmah Laili; Abdullah, Siti Alida John; Ayub, Zainal Amin; Azhar, Alias (Medwell Publishing, 2017)
This study aims to explore factors that determine youth participation in decision making in the youth development programmes as a means of participation of young people in the creation and involvement of their own destinies. A survey has been conducted among youth in Malaysia to investigate their perception of their ability to participatein decision-making for the youth development programmes. The study is based on a quantitative approach. The data were collected through a survey among 340 respondents. It offers to understand characteristics of factors that influence youth to participate in decision-making about youth development programmes. The study found three factors which measure the elements that lead youth to participate in decision-making related to youth development programmes contexts. Moreover, scores on the scale developed to measure the factors influencing youth to participate in decision-making yielded excellent validity and reliability estimates